HUBUNGAN TINGKAT PENGETAHUAN ORANGTUA TENTANG STIMULASI VERBAL DENGAN PERKEMBANGAN BAHASA PADA ANAK USIA DINI DI TK YAYASAN BHAKTI SIWI DESA SORAN KABUPATEN KLATEN - Rahayu Setyaningsih; Neri Anggasari (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Background : children who experience language disorders in preschool 40% to 60% willhave learning difficulties in writing and academic subjects. Information from one of theparents of students in kindergarten Yayasan Bhakti Siwi Soran village during the2016/2017 school year in which students in the kindergarten were 32 students, 9 ofthem have not been able to use words that are obvious in everyday communication,some parents provide stimulation to train their children to talk, some parents motivatefor daring to express their opinions, but there are also parents not know how tostimulate children who have a language disorder.Purpose of the study: to determine the relationship of the level of parental knowledgeabout verbal stimulation with language development in early children at the TK YayasanBhakti Siwi Soran village.Methods : the research design correlation with cross sectional approach. Subject were32 student with mother. Data obtained by questionaire to determine level of parentalknowledge with language development. Data analyzed with Chi Square test p=0.05.Results : based on the test results of the bivariate analysis using Chi-Square with Î± =5% (0.05) was obtained p <0.001 to p <0.05, which means the hypothesis is accepted.Conclusion : there is the correlation between parental knowledge about verbalstimulation with language development in children.Keywords: Knowledge, Verbal Stimulation, Language Development